2015
DOI: 10.1515/bima-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Renewable chitin from marine sponge as a thermostable biological template for hydrothermal synthesis of hematite nanospheres using principles of extreme biomimetics

Abstract: range of uses. Here, chitin-based scaffolds isolated from the skeleton of marine demosponge Aplysina aerophoba were used as a template for the in vitro formation of iron oxide from a saturated iron(III) chloride solution, under hydrothermal conditions (pH~1.5, 90 °C). The resultant chitin-Fe 2 O 3 three dimensional composites, prepared for the first time via hydrothermal synthesis route, were thoroughly characterized using light, fluorescence and scanning electron microscopy; as well as with analytical methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…The intensity and full width at half maximum (FWHM) values of thev 1 (CO 3 2− ) stretching mode indicated the highest calcite crystallinity in red dactyls, followed by green dactyls, white, and blue palm shells. Significant broadening of the v 1 mode to the lower wavenumbers, paired with broadening of the v 4 and lattice modes indicates the co-existence of amorphous 37 CaCO 3 in blue and white shells, while broadening of v 1 to higher wavenumbers indicates small inclusions of Mg atoms in calcite crystalline lattice 36 . The area ratio r of the two Raman band components of calcite stretching mode in blue shell showed a value r = area (1085) /area (1075) of 2.82 ( Supplementary Fig.…”
Section: Blue and Green Shells Turn Red-orange When Immersed In Boilimentioning
confidence: 99%
“…The intensity and full width at half maximum (FWHM) values of thev 1 (CO 3 2− ) stretching mode indicated the highest calcite crystallinity in red dactyls, followed by green dactyls, white, and blue palm shells. Significant broadening of the v 1 mode to the lower wavenumbers, paired with broadening of the v 4 and lattice modes indicates the co-existence of amorphous 37 CaCO 3 in blue and white shells, while broadening of v 1 to higher wavenumbers indicates small inclusions of Mg atoms in calcite crystalline lattice 36 . The area ratio r of the two Raman band components of calcite stretching mode in blue shell showed a value r = area (1085) /area (1075) of 2.82 ( Supplementary Fig.…”
Section: Blue and Green Shells Turn Red-orange When Immersed In Boilimentioning
confidence: 99%
“…For example, Ehrlich et al used an extreme biomimetic strategy to develop a zirconium oxide phase on the surface of chitin, which is thermostable up to 400 °C [ 91 ]. This approach has also been used to create novel multiphase composites, such as chitin/zirconia [ 90 ], β-chitin/ZnO [ 137 ], chitin/GeO 2 [ 138 ], chitin/hematite [ 139 , 140 ], chitin/(Ti,Zr)O 2 [ 141 ], chitin/silica [ 142 , 143 ] and chitin/POSS [ 144 ], for various applications. Recently, an extreme biomimetic route was also used for the first time for the development of pectin/GeO 2 composites [ 145 ].…”
Section: Spongin and Extreme Biomimeticsmentioning
confidence: 99%
“…Especially, some recent studies reported by Ehrlich et al have provided new insights into the nature and function of chitin found in the organisms of phylum Porifera [15][16][17][18]. The authors isolated three dimensional chitin structures from sponges, and they had excellent results regarding applications of those chitin isolates [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%